Binder composition for agglomerating iron ore
By using an adhesive composition containing specific organic and inorganic adhesives, the problem of excessive viscosity and dust pollution of the iron mineral ball ball in the iron mineral group, and achieved the effect of smooth surface and excellent mechanical performance.
Patent Information
- Application Number
- CN202380040248.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-24
- Filing Date
- 2023-05-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-05-16
AI Technical Summary
The adhesives of existing iron ore pellets have dust pollution problems, which leads to excessive viscosity of the pellet surface, which easily leads to dust being blown out, causing pollution and equipment wear.
Adopting an adhesive composition, including at least two organic adhesives (water-soluble anionic polymer P1 and water-soluble anionic or amphoteric polymer P2) and at least one inorganic adhesive (such as sodium carbonate), these adhesives The mixture has a specific particle size and proportion, making the surface of the pellets smooth and reducing dust pollution.
The surface of the pellets is smooth, dust pollution is reduced, the mechanical properties and production efficiency of the pellets are improved, and equipment wear and pollution problems are avoided.
Smart Images

Figure BDA0005132106780000111 
Figure BDA0005132106780000121
Abstract
Description
Technical Field
[0001] The present invention relates to a binder composition for the manufacture of iron ore pellets. More specifically, the binder composition contains at least two organic binders and at least one inorganic binder. These binders have specific properties. Prior art
[0002] Iron ore should be in the form of large pellets when it is charged into the blast furnace. If the ore is in the form of pellets and these pellets are too small to be charged directly into the blast furnace, they must be processed into pellets. As low-grade ores are increasingly used, it is necessary to grind the ore finer. Pelletizing (or granulation) is the only satisfactory way to produce furnace charge from these fine particles.
[0003] Pellets are made by adding a binder to a fine-grained ore and stirring it in the presence of a small amount of water (usually the moisture in the ore) to form a wet mixture, which is then shoveled into a pelletizing drum or disc pelletizer, for example. The green pellets (or green pellets, as they are called before they are sintered by firing) are then fired in a furnace at a range of temperatures, from an inlet temperature of typically 200 to 400 degrees Celsius to a final high temperature (e.g., 1,200 degrees Celsius).
[0004] Important pellet properties include the initial or wet strength, the dry strength (after drying the green pellets in a furnace at 105°C), and the tendency of the pellets to brittle (or burst or flake) when exposed to the firing temperature of the furnace. The tendency to flake can be defined by determining the lowest temperature at which flakes occur, or by observing the percentage of fines formed during a specific firing cycle. The moisture content of the mixture and the porosity of the pellets must be carefully selected. It is desirable for the green pellets to have a high "drop number". For cost reasons, the amount of binder should be as low as possible, and to ensure uniform properties, its flow properties should be such that the binder can be added uniformly and easily in such small amounts.
[0005] Binders are traditionally clays (usually bentonite), cements (usually Portland cement) or lime. However, there have been various proposals to use organic polymers as binders. Thus, natural polymers, in particular cellulosic polymers, have been considered, but they are not entirely satisfactory. In fact, it can be quite difficult to precisely regulate their addition to the granular material. Synthetic polymers (usually water-soluble linear anionic polymers with a molecular weight of 1 to 20 million in powder form) have also been proposed for many years, but their use also presents difficulties.
[0006] For example, WO 2017 / 037207 discloses a binder composition comprising a water-soluble polymer with a molecular weight of 1,000 to 20,000 Da, a copolymer with a molecular weight greater than 300,000 Da, and an inorganic pelletizing aid. In the same field, US5002607 describes a binder composition comprising a water-soluble polymer with a molecular weight less than 50,000 Da, a binder polymer with a molecular weight greater than 1 million Da, and an inorganic pelletizing aid.
[0007] The size of the polymer particles is usually relatively large, usually greater than 700 μm. The results obtained with these large particle size products are not entirely satisfactory. In fact, the pellets obtained tend to be contaminated with dust adhering to their surface, which is subsequently blown off during the metallurgical use of the pellets. It is believed that this problem is due to the surface of the pellets being stickier than ideal. Whatever the cause, the disadvantage of the pellets is that when the air is blown through the pellet bed, metal ore dust can be entrained in the air and carried out of the furnace. This can cause contamination problems and cause undesirable wear on the fan and other parts of the furnace and related equipment.
[0008] In patents EP 0225171 and EP 288150, specific synthetic polymers are proposed, the dry particle size of which must be between 20 and 300 μm. This size is preferably less than 100 μm and the proportion by weight is at least 50%.
[0009] Using smaller particles tends to provide better granulation properties (including reduced dust problems), but leads to some handling problems. These particles are usually ground gel particles. However, handling very small broken gel particles also poses problems of its own. On the one hand, because there is a risk of polymer fines being blown away during the mixing step, on the other hand, because the flow properties of the particles are not entirely satisfactory and, finally, because there may be difficulties in metering the particles accurately into the granulated material. Summary of the invention
[0010] The applicant has surprisingly found a binder composition for the manufacture of iron ore pellets, containing at least two organic binders and at least one inorganic binder, which binders have specific properties that make it possible to maintain satisfactory pelletizing performance, minimize dust problems, facilitate handling properties, and allow the use of large polymer particles. In addition, within the scope of the present invention, the pellets can have a more uniform shape than when using binders based on other polymers.
[0011] More specifically, the present invention relates to a binder composition for use in the manufacture of iron ore pellets, comprising:
[0012] a) at least two organic binders LO in solid particulate form, which are at least:
[0013] - a water-soluble anionic polymer P1 having a weight average molecular weight of 500 to 200,000 Daltons, and
[0014] - a water-soluble anionic or amphoteric polymer P2 having a weight average molecular weight greater than 500,000 Daltons; and
[0015] b) at least one inorganic binder LI in the form of solid particles,
[0016] The solid particles of the binder LO have a number median particle size greater than 500 microns,
[0017] The number median particle size of the particles of binder LI is less than one third of the number median particle size of the solid particles of binder LO.
[0018] Thus, the bonding composition comprises a mixture of an anionic water-soluble polymer P1, an anionic or amphoteric water-soluble polymer P2, and an inorganic binder LI.
[0019] Another aspect of the present invention relates to iron ore pellets containing 50 to 5000 ppm of the binder composition of the present invention.
[0020] The term "polymer" refers to homopolymers and copolymers of at least two different monomers.
[0021] As used herein, the term "water-soluble polymer" is understood to mean a polymer that, when dissolved in 20 g / L at 25°C, -1 When dissolved in deionized water and stirred for 4 hours, an aqueous solution without insoluble particles was obtained.
[0022] Numerical ranges include lower and upper limits. Thus, the numerical ranges of "0.1 to 1.0" and "from 0.1 to 1" include the values 0.1 and 1.0.
[0023] According to the invention, the weight average molecular weight of the water-soluble polymers P1 and P2 is determined by measuring the intrinsic viscosity. The intrinsic viscosity can be measured by methods known to those skilled in the art and can in particular be calculated from the reduced viscosity values at different concentrations by a graphical method, which consists in plotting the reduced viscosity values (on the ordinate axis) as a function of the concentration (on the abscissa axis) and calculating by extrapolating the curve to zero concentration. The intrinsic viscosity values are read on the ordinate axis or using the least squares method. The weight average molecular weight can then be determined by the Mark-Houwink equation:
[0024] [η] = KM α
[0025] [η] represents the intrinsic viscosity of the polymer as determined by solution viscometry,
[0026] K represents the empirical constant,
[0027] M represents the molecular weight of the polymer,
[0028] α represents the Mark-Houwink coefficient,
[0029] α and K depend on the specific polymer-solvent system. Tables known to the person skilled in the art give the values of α and K as a function of the polymer-solvent system.
[0030] The weight average molecular weight of the water-soluble polymer P1 is from 500 to 200,000 Daltons, more preferably from 1,000 to 50,000 Daltons, even more preferably from 1,000 to 10,000 Daltons.
[0031] The weight average molecular weight of the water-soluble polymer P2 is greater than 500,000 Daltons, more preferably greater than 1 million Daltons. The weight average molecular weight of the water-soluble polymer P2 is generally less than 40 million Daltons, preferably less than 30 million Daltons.
[0032] The water-soluble polymer P1 is anionic and therefore contains anionic monomers and optionally nonionic monomers.
[0033] Advantageously, polymer P1 contains from 50 to 100 mol %, more preferably from 70 to 100 mol %, even more preferably from 90 to 100 mol % of anionic monomers.
[0034] The nonionic monomers of the water-soluble polymer P1 are preferably selected from acrylamide, methacrylamide, N-alkyl acrylamide, N-alkyl methacrylamide, N,N-dialkyl acrylamide, N,N-dialkyl methacrylamide, alkoxylated acrylic acid esters, alkoxylated methacrylic acid esters, N-vinyl pyridine, N-vinyl pyrrolidone, hydroxyalkyl acrylates, hydroxyalkyl methacrylates and mixtures thereof. In these nonionic monomers, the alkyl groups are advantageously C1-C5, more advantageously C1-C3. They are preferably straight-chain alkyl groups.
[0035] The anionic monomer of the water-soluble polymer P1 is preferably selected from monomers having carboxylic acid functional groups and their salts, including acrylic acid, methacrylic acid, itaconic acid, and maleic acid; monomers having sulfonic acid functional groups and their salts, including acrylamide-tert-butylsulfonic acid (ATBS), allyl sulfonic acid, methallyl sulfonic acid and their salts; and monomers having phosphonic acid functional groups and their salts.
[0036] The salt may be an alkali metal salt or an alkaline earth metal salt. The term "alkali" is to be understood as an alkali metal, advantageously lithium, sodium or potassium. The term "alkaline earth" is to be understood as an alkaline earth metal, advantageously calcium or magnesium.
[0037] Preferably, polymer P1 is a polymer of at least one anionic monomer comprising at least one carboxylate functional group -C(=O)-O - X + , wherein X is an alkali metal, and at least one carboxylate functional group -C(=O)-O - X' + , wherein X' is an alkaline earth metal.
[0038] This does not therefore exclude the presence of anionic monomers containing carboxylic acid functionality (not neutralized) in polymer P 1. In other words, it is possible for anionic monomers having carboxylic acid functionality and the same monomers having carboxylate functionality to be present simultaneously.
[0039] Advantageously, when the anionic monomers of polymer P1 are present both in their carboxylic acid form and in their carboxylate form, the proportion of the carboxylate form is from 10 to 100 mol %, more advantageously from 20 to 100 mol %, relative to the sum of carboxylate and carboxylic acid form.
[0040] Advantageously, 40 to 60 mol % of the carboxylate functions of polymer P1 are neutralized with alkali metal salts and 40 to 60 mol % of the carboxylate functions are neutralized with alkaline earth metal salts.
[0041] Even more preferably, the at least one anionic monomer containing a carboxylate function of polymer P1 is an acrylate.
[0042] The polymer P1 is advantageously a polymer of a mixture of at least an alkali metal salt, advantageously sodium, and an alkaline earth metal salt, advantageously calcium, of acrylic acid CH2=CH-C(=O)OH.
[0043] According to a preferred embodiment, the carboxylate functions of polymer P1 are neutralized with sodium and calcium.
[0044] Advantageously, polymer P1 contains at least sodium acrylate and calcium acrylate.
[0045] The polymer P1 may be linear or structured by at least one structurant which may advantageously be chosen from polyethylenically unsaturated monomers (having at least two unsaturated functional groups), such as vinyl, allyl, acrylic and epoxy functional groups, and mention may be made, for example, of sodium allyl sulfonate, sodium methallyl sulfonate, sodium methallyl disulfonate, methylenebisacrylamide, diallylamine, triallylamine, triallylammonium chloride, tetraallylammonium chloride, or structured by macroinitiators, such as polyperoxides, polyazoics, and polytransfer agents, such as polymercaptanpolymers or hydroxyalkylacrylates and ethylene oxide.
[0046] The polymer P1 can also be structured using controlled radical polymerization technology (CRP, short for “Controlled Radical Polymerization”), or more specifically using RAFT-type technology (short for “Reversible Addition Fragmentation Chain Transfer”).
[0047] The solid polymer particles P1 are in the form of powders. These particle forms are obtained by techniques known to those skilled in the art.
[0048] The polymer P1 can be obtained in powder form by polymerization in aqueous solution followed by drum drying, spray drying, radiation drying (eg microwave drying) or fluidized bed drying.
[0049] Preferably, polymer P1 is in powder form, obtained by polymerization in aqueous solution and subsequent drum drying.
[0050] The polymerization to obtain the polymer P1 according to the invention is generally carried out by a free radical route. This includes free radical polymerization using UV, azo, redox or thermal initiators, as well as CRP or more specifically RAFT type polymerization techniques.
[0051] During the polymerization of polymer P1, several additives known to those skilled in the art (azo compounds, redox couples, transfer agents, terminators, etc.) may be advantageously added. Some of these may contain sulfur, such as sodium bisulfite, sodium metabisulfite or sodium persulfate.
[0052] The polymerization of polymer P1 can be initiated in the presence of an oxidation / reduction couple. A preferred sulfur-containing oxidizing agent is sodium persulfate.
[0053] Preferably, polymer P1 contains at most 2% by weight of sulphur, more preferably at most 1% by weight of sulphur derived from sodium bisulfite, and / or sodium pyrosulfite, and / or sodium persulfate.
[0054] “A and / or B” means A, or B, or A and B.
[0055] The water-soluble polymer P2 is an anionic or amphoteric polymer and therefore contains anionic monomers, optionally cationic monomers, and optionally nonionic monomers.
[0056] The nonionic monomer of the water-soluble polymer P2 is preferably selected from acrylamide, methacrylamide, N-alkyl acrylamide, N-alkyl methacrylamide, N,N-dialkyl acrylamide, N,N-dialkyl methacrylamide, alkoxylated acrylic acid esters, alkoxylated methacrylic acid esters, N-vinyl pyridine, N-vinyl pyrrolidone, hydroxyalkyl acrylates, hydroxyalkyl methacrylates and mixtures thereof. In these nonionic monomers, the alkyl group is advantageously C1-C5, more advantageously C1-C3. They are preferably straight-chain alkyl groups. The nonionic monomer is preferably acrylamide.
[0057] The anionic monomer of the water-soluble polymer P2 is preferably selected from monomers with carboxylic acid functional groups and their salts, including acrylic acid, methacrylic acid, itaconic acid, maleic acid; monomers with sulfonic acid functional groups and their salts, including acrylamide-tert-butylsulfonic acid (ATBS), allylsulfonic acid, methallylsulfonic acid and their salts; and monomers with phosphonic acid functional groups and their salts. Preferred anionic monomers are acrylic acid and its salts.
[0058] The salt may be an alkali metal salt or an alkaline earth metal salt. Advantageously, the alkali metal is sodium.
[0059] The cationic monomer of the water-soluble polymer P2 is preferably selected from quaternized or salified dimethylaminoethyl acrylate (ADAME), quaternized or salified dimethylaminoethyl methacrylate (MADAME), diallyldimethylammonium chloride (DADMAC), acrylamidopropyltrimethylammonium chloride (APTAC) and methacrylamidopropyltrimethylammonium chloride (MAPTAC).
[0060] Advantageously, the cationic monomer of polymer P2 has a halogen as counterion, preferably a chloride ion. A preferred cationic monomer is dimethylaminoethyl acrylate (ADAME) quaternized with methyl chloride.
[0061] Preferably, polymer P2 is a copolymer of acrylamide and sodium acrylate.
[0062] The polymer P2 may be linear or structured by at least one structurant which may advantageously be chosen from polyethylenically unsaturated monomers (having at least two unsaturated functional groups), such as vinyl, allyl, acrylic and epoxy functional groups, and mention may be made, for example, of sodium allyl sulfonate, sodium methallyl sulfonate, sodium methallyl disulfonate, methylenebisacrylamide, diallylamine, triallylamine, triallylammonium chloride, tetraallylammonium chloride, or structured by macroinitiators, such as polyperoxides, polyazo compounds, and polytransfer agents, such as polymeric thiol polymers or hydroxyalkyl acrylates and ethylene oxide.
[0063] The polymer P2 can also be structured using CRP polymerisation techniques or more specifically RAFT-type techniques.
[0064] Advantageously, the structure of polymer P2 is star-shaped, having a central part (core) and polymer-based arms extending radially from said central part.
[0065] The water-soluble polymer P2 is advantageously a copolymer of at least one nonionic monomer, advantageously acrylamide, and at least one anionic monomer, advantageously acrylic acid and / or its salts.
[0066] The polymer microgel advantageously comprises 0 to 100 mol% of cationic monomers, preferably 0 to 80 mol%, more preferably 0 to 60 mol%, even more preferably 0 to 50 mol%. Specifically, polymer P2 preferably comprises 5 to less than 100 mol% (except 100%), more preferably 10 to 80 mol%, even more preferably 20 to 60 mol% of sodium acrylate; and greater than 0 to 95 mol% (except 0%), more preferably 20 to 90 mol%, even more preferably 40 to 80 mol% of acrylamide.
[0067] The solid particles of polymer P2 are in the form of powder or microbeads. These particle forms are obtained by techniques known to those skilled in the art.
[0068] The polymer P2 can be obtained in powder form by gel polymerization, aqueous solution polymerization followed by drum drying, spray drying or radiation drying (eg microwave drying) or fluidized bed drying.
[0069] The powder form of the water-soluble polymer P2 can also be obtained by water-in-oil emulsion polymerization (inverse emulsion), followed by a distillation / concentration step and spray drying of the resulting liquid.
[0070] The P2 polymer microbeads are advantageously obtained by inverse suspension polymerization.
[0071] Preferably, polymer P2 is in the form of a powder obtained by gel polymerization or in the form of microbeads obtained by inverse suspension polymerization.
[0072] The polymerization to obtain the polymer P2 of the invention is carried out by a free radical route. It includes free radical polymerization using UV, azo, redox or thermal initiators, as well as CRP or more specifically type polymerization techniques.
[0073] The adhesive composition of the present invention also comprises an inorganic binder LI. The LI binder is advantageously a non-polymer. It is preferably selected from sodium carbonate, sodium bicarbonate, sodium phosphate, sodium silicate, urea, calcium oxide, bentonite and mixtures thereof.
[0074] Preferably, the adhesive composition consists of P1+P2+LI and comprises:
[0075] - 2 to 40% by weight of polymer P1,
[0076] - 20 to 60% by weight of polymer P2, and
[0077] - 30 to 70% by weight of binder LI,
[0078] The sum of the weight percentages of P1+P2+LI equals 100%.
[0079] More preferably, the adhesive composition contains:
[0080] - 5 to 30% by weight of polymer P1,
[0081] - 25 to 55% by weight of polymer P2, and
[0082] - 35 to 65% by weight of binder LI,
[0083] The sum of the weight percentages of P1+P2+LI equals 100%.
[0084] Even more preferably, the adhesive composition comprises:
[0085] - 8 to 25% by weight of polymer P1,
[0086] - 35 to 50% by weight of polymer P2, and
[0087] - 40 to 60% by weight of binder LI,
[0088] The sum of the weight percentages of P1+P2+LI equals 100%.
[0089] According to the present invention, the binders LO (P1 and P2) and the binder LI are in the form of solid particles, such that the median particle size (D 50) is greater than 500 microns, and the number median particle size of the particles of binder LI is less than one-third of the number median particle size of the solid particles of binder LO.
[0090] The number median particle size (D 50 ) is defined as the largest dimension of a particle (the diameter for spherical particles) such that half of the particles in a population (half the number of particles) have a size below this value.
[0091] For spherical particles, the particle size refers to the average diameter measured using a laser diffraction particle analyzer according to conventional techniques of those skilled in the art. An example of an instrument for measuring particle size is the Mastersizer from Malvern Instruments.
[0092] Advantageously, the organic binder LO has a number median particle size of 500 to 5000 microns, more preferably 500 to 2000 microns.
[0093] The adhesive composition according to the present invention is usually formed by simply mixing its ingredients, each of which is in powder form.
[0094] Finally, the last aspect of the present invention relates to an iron ore pellet comprising 50 to 5000 ppm of a binder composition based on the weight of the iron ore pellet.
[0095] The granules are typically prepared by adding the binder composition to finely divided ore and stirring in the presence of a small amount of water (preferably moisture from the ore) to form a wet mixture which is then pelletized (pelletized) such as in a pelletizing drum or disc pelletizer.
[0096] The invention is illustrated by the following examples without limiting its scope. Example
[0097] Synthesis of P1 polymer
[0098] The P1 polymer is obtained by a method known to those skilled in the art for the polymerization of acrylic acid in aqueous solution. The monomers are introduced into a heated reactor by casting, at which time also the initiator and transfer agent solutions are introduced. The initiator solution is composed of a combination of ammonium persulfate and sodium bisulfite as a reducing agent. The proportion of sulfur in all the components involved in the process is strictly less than 2% by weight of the total formulation. The polymer P1 is neutralized with soda to obtain sodium counterions, or with soda and calcium oxide (50 / 50 by weight) to obtain sodium and calcium counterions of different nature. This neutralization is carried out on the polymer before the end of the polymerization. At the end of the polymerization, the polymer solution is drum dried to obtain the P1 polymer in the form of a powder.
[0099] Therefore, four tests were performed and four P1 polymers were synthesized, namely P1-A (according to the invention), P1-B (according to the invention), P1-C (comparative example) and P1-D (comparative example).
[0100] Synthesis of P2 polymer
[0101] The polymer P2 is obtained from acrylamide and sodium acrylate by gel polymerization as known to the person skilled in the art. At the end of the polymerization, the polymer gel is granulated, dried, ground and sieved to give the polymer P2 in the form of a powder.
[0102] Therefore, four tests were performed and four P2 polymers were synthesized, namely P2-A (according to the invention), P2-B (according to the invention), P2-C (comparative example) and P2-D (comparative example).
[0103] Pellet manufacturing
[0104] In the following examples, green iron ore pellets containing various compounds in amounts shown in Table 1 were prepared. The green pellets were prepared by agglomerating iron ore concentrate in the presence of a binder composition. The amount of binder (in weight percent) shown in Table 1 is based on the total weight of the iron ore concentrate. The iron ore concentrate used in the examples of Table 1 was Brazilian hematite concentrate.
[0105] The inorganic binder LI used was sodium carbonate obtained from two different sources: LI-1 (according to the invention) and LI-2 (comparative example).
[0106] As described in Table 2, various comparative adhesive compositions (CEX 1 to CEX 12) and (C1 to C5) of the present invention were prepared. They all consisted of an inorganic binder LI and two organic binders, the organic binders being previously synthesized polymers P1 and P2. In each case, the adhesive composition was prepared by compounding using a homogenized mixture of the three components.
[0107] The manufacturing process of green ore pellets is generally known to the person skilled in the art.We produced different green ore pellets to test different binder compositions.
[0108] First, the binder composition was mixed into the dry mineral concentrate and homogenized with the required amount of water (8 to 9% moisture content by weight).The mineral concentrate was mixed with the binder composition using a KitchenAid mixer.
[0109] Next, pellet precursors (or seeds) are formed by placing a small portion of the previously obtained ore concentrate and binder composition into a rotating pelletizing tire (about 40 cm in diameter) and adding atomized water to initiate pellet growth. Pellet seeds with a size of 2.5 to 4 mm are thus formed.
[0110] Then, finished green pellets with a size of 9.5 to 12.5 mm are obtained by placing 55 grams of pellet seeds in a rotating pelletizing disk and adding part of the remaining mixture (mineral concentrate + binder composition) during a growth period of 5 to 6 minutes. If necessary, atomized water can be added.
[0111] The moisture content, ball drop number, and wet and dry compressive strength of the green pellets obtained in each case were measured and the results are summarized in Table 3.
[0112] Number of wet balls (NWD)
[0113] The wet ball number is determined by repeatedly dropping wet green pellets with a particle size of 11.2 to 12.5 mm from a height of 46 cm onto a horizontal steel plate until the pellets break. Visible cracks form on the surface of the pellets. The number of times required for the pellets to reach their breaking / cracking point is determined. This measurement is performed on 20 pellets. The average of these 20 measurements is called the wet ball number (NWD).
[0114] Wet compressive strength (WCS)
[0115] 20 wet green pellets with a particle size of 11.2 to 12.5 mm are stored in a closed container. The pellets are removed one by one and placed in a standard ANDILOG brand measuring device. The maximum force applied when the pellet breaks is determined. The average of these 20 measured values is called the "wet compressive strength" (WCS).
[0116] Dry Compression Strength (DCS)
[0117] 20 green pellets with a particle size of 11.2 to 12.5 mm are dried in an oven at 105°C for at least two hours. After drying, the dried pellets are placed one by one in a standard ANDILOG brand measuring device. The maximum force applied when the pellet breaks is determined. The average of these 20 measurements is called the "Dry Compression Strength" (DCS)
[0118] Table 1: Organic binders and inorganic binders
[0119]
[0120] Table 2: Amounts of binder and minerals required to obtain green pellets
[0121]
[0122] Table 3: Physical properties of green pellets
[0123] test Surface appearance of pellets NWD WCS(kg) DCS(kg) C1 Smooth and shiny 4.5 1:35 6.3 C2 Smooth and shiny 4.9 1.3 4.9 C3 Smooth and shiny 6.5 1.3 5.1 C4 Smooth and shiny 6 1.3 4.2 C5 Smooth and shiny 6 1.3 4.7 CEX1 Slightly grainy - matte 2.9 1.4 6.2 CEX2 Very grainy (orange peel-like) 4.2 1 2.9 CEX3 Very grainy (orange peel-like) 4 1.2 2.7 CEX4 Smooth and very wet-sticky 3.5 1 1.8 CEX5 Very grainy (orange peel-like) + has holes 3.8 1 1.7 CEX6 Smooth and too wet - very sticky 3.1 0.85 1.65 CEX7 Smooth and very wet-sticky 3.2 0.9 1.85 CEX8 Very grainy (orange peel-like) + has holes 4 1 1.95 CEX9 Very grainy (orange peel-like) + has holes 4.2 1 2 CEX10 Very grainy (orange peel-like) + has holes 1 0.3 0.85 CEX11 Slightly grainy (orange peel) – matte 3,2 1,3 3,0 CEX12 Very grainy (orange peel-like) 3,5 1 2,5
[0124] Table 3 shows that the green pellets of Examples C1 to C5 using the binder composition of the present invention have smoother surfaces than the green pellets of Comparative Examples CEX 1 to CEX 12.
[0125] Improving the surface condition of pellets is very important to industrial manufacturers, as grainy and / or non-smooth surfaces can lead to increased wear and tumbling indices, resulting in a reduction in the marketable size of the pellets and increased dust levels in the furnace and during handling.
[0126] The dry compression strength tested for the binder compositions C1 to C5 according to the invention is improved compared to the tests for the comparative binder compositions CEX 1 to CEX 12. This parameter is very important for industrial manufacturers since it allows to determine the behavior of the pellets in the furnace: a higher dry compression strength will avoid the crushing of the pellets in the bed and will produce harder pellets.
[0127] In contrast, composition C3 can improve NWD and DCS compared to adhesive composition C5. Thus, the counterion selection of polymer P1 affects the physical properties of the pellets.
[0128] From the testing of comparative adhesive compositions CEX 2, CEX 3 and CEX 4, it was observed that the molecular weight selection of polymers P1 and P2 is very important to obtain a smooth pellet surface and good physical properties.
[0129] Testing of the comparative binder composition CEX 5 shows that the ratio between the particle size of the organic binder and the particle size of the inorganic binder is critical. If this ratio is outside the required range, the surface of the resulting pellets is too brittle and therefore easily broken.
[0130] The amount of each binder in the green pellets is also an important criterion, as shown by the tests of the comparative binder composition CEX 6. If these amounts are outside the required range, the pellets will be very sticky (which will lead to a decrease in productivity) and will not be strong enough for industrial manufacturers.
[0131] Testing of comparative binder compositions CEX 7, CEX 8 and CEX 9 shows that the presence of at least two organic binders, polymer P1 and polymer P2, is essential. Without one of these two polymers, the surface of the pellets is not smooth and the physical properties are unsatisfactory.
[0132] Testing of the comparative binder composition CEX 10 shows that the presence of the organic binder LO is extremely important. Without the organic binder (only the inorganic binder LI is present), the surface of the pellets is not smooth and does not have satisfactory mechanical properties.
[0133] Finally, comparative adhesive compositions CEX 11 and CEX 12 show that when the median particle size D of polymer P1 or polymer P2 is 50 Below 500 μm, the surface of the pellets is not smooth and does not have satisfactory mechanical properties.
Claims
1. A binder composition for producing iron ore pellets, the binder composition comprising: a) at least two organic binders LO in solid particulate form, which are at least: - a water-soluble anionic polymer P1 having a weight average molecular weight of 500 to 200,000 Daltons, and - a water-soluble anionic or amphoteric polymer P2 having a weight average molecular weight greater than 500,000 Daltons; and b) at least one inorganic binder LI in the form of solid particles, The solid particles of the binder LO have a number median particle size greater than 500 microns, The number median particle size of the particles of binder LI is less than one third of the number median particle size of the solid particles of binder LO.
2. The adhesive composition according to claim 1, characterized in that The polymer P1 is a polymer of at least one anionic monomer comprising (1) at least one carboxylate functional group -C(=O)-O - X + , wherein X is an alkali metal, and (2) at least one carboxylate functional group -C(=O)-O - X' + , wherein X' is an alkaline earth metal.
3. The adhesive composition according to claim 2, characterized in that The polymer P1 is at least a polymer of a mixture of alkali metal and alkaline earth metal salts of acrylic acid CH2=CH-C(=O)OH.
4. The adhesive composition according to claim 2 or 3, characterized in that The alkali metal is sodium, and the alkaline earth metal is calcium.
5. The adhesive composition according to any one of the preceding claims, characterized in that The polymer P1 contains at most 2% by weight of sulfur originating from sodium bisulfite and / or sodium metabisulfite and / or sodium persulfate.
6. The adhesive composition according to any one of the preceding claims, characterized in that Polymer P2 is a copolymer of acrylamide and sodium acrylate.
7. The adhesive composition according to any one of the preceding claims, characterized in that Polymer P2 is a copolymer containing 5 mol % to less than 100 mol % of sodium acrylate and greater than 0 mol % to 95 mol % of acrylamide.
8. The adhesive composition according to any one of the preceding claims, characterized in that The inorganic binder LI is selected from the group consisting of sodium carbonate, sodium bicarbonate, sodium phosphate, sodium silicate, calcium oxide, bentonite and mixtures thereof.
9. The adhesive composition according to any one of the preceding claims, characterized in that It preferably consists of P1+P2+LI, and it contains: - 2 to 40% by weight of polymer P1, - 20 to 60% by weight of polymer P2, - 30 to 70% by weight of binder LI, The total weight percentage of P1+P2+LI is equal to 100%.
10. Iron ore pellets, comprising 50 to 5000 ppm of the binder composition according to any one of claims 1 to 9, based on the weight of the iron ore pellets.
Citation Information
Patent Citations
Iron ore pelletisation
EP0225171A2
Ore pelletisation
EP0288150A1
Process for pelletizing particulate materials
US5002607A
Use of hydrophobically associating copolymers as binders for pelletizing metal containing ores
WO2017037207A1
Use of copolymers as binders for pelletizing metal containing ores
CN110249064A